2007
DOI: 10.1029/2006jb004308
|View full text |Cite
|
Sign up to set email alerts
|

Seismic study of the transform‐rifted margin in Davis Strait between Baffin Island (Canada) and Greenland: What happens when a plume meets a transform

Abstract: The Davis Strait transform margin was studied using a 630‐km‐long wide‐angle reflection/refraction seismic transect extending from SE Baffin Island to Greenland. Dense airgun shots were recorded by 28 ocean bottom seismometers deployed along the line. A P wave velocity model was developed from forward and inverse modeling of the wide‐angle data and incorporation of coincident deep multichannel reflection seismic data. Off Baffin Island in the Saglek Basin, 7 to 11‐km‐thick two‐layered continental crust (5.8–6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
137
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(154 citation statements)
references
References 47 publications
16
137
1
Order By: Relevance
“…Keen et al (2012) showed that the Labrador Sea is exemplified by the presence of excess magmatism, SDRs, and volcanic plateau and thick igneous crust. This agrees with the classification of Funck et al (2007) and Gerlings et al (2009).…”
Section: Magmatism and Influence Of The Mantle Plumesupporting
confidence: 82%
See 4 more Smart Citations
“…Keen et al (2012) showed that the Labrador Sea is exemplified by the presence of excess magmatism, SDRs, and volcanic plateau and thick igneous crust. This agrees with the classification of Funck et al (2007) and Gerlings et al (2009).…”
Section: Magmatism and Influence Of The Mantle Plumesupporting
confidence: 82%
“…............... 48 , Funck et al (2007Funck et al ( , 2012, and Suckro et al (2012Suckro et al ( , 2013. Serpentinite zone from Nafe-Drake polynomial curve was interpreted in Baffin Bay, , Funck et al (2007Funck et al ( , 2012, and Suckro et al (2012Suckro et al ( , 2013. Serpentinite zone from Nafe-Drake polynomial curve was interpreted in Baffin Densities were then calculated as a function of velocities using four different methods and in comparison with published data of , Funck et al (2007Funck et al ( , 2012, and Suckro et al (2012Suckro et al ( , 2013.…”
Section: List Of Figuresmentioning
confidence: 99%
See 3 more Smart Citations